The Gen Z micro-influencer experience - Guzman, Sandra (Kansas State University, 2024)
According to Meltwater (2022), micro-influencers allow brands to boost brand awareness, impression, and increase engagement and conversation among consumers. Micro-influencers are content creators who have a small platform on social media: between 10,000 and 100,000 followers (Meltwater, 2022). They’re often experts on a specific industry, skill, or topic and have a highly engaged online community that they form. Micro-influencers enable brands to connect with individual users through their personal social media accounts. Micro-influencers are an important aspect to the public relations field due to their highly trusted social media content that shapes the way users view a brand or product. Information that is widely spread through micro-influencers' social platforms can have major effects on brand awareness and help facilitate a positive public perception (Tsugawa & Ohsaki, 2017). The lack of research on Gen Z micro-influencers as a public relations strategy, and their experiences towards crafting their influencer brand from scratch, opens a unique window for understanding their journey. While past research points to the power of micro-influencers over mega-influencers (Park et. al., 2021), little is known about how Gen Z micro-influencers gain their knowledge to perfect their online personas and how it affects their self-confidence. This study aims to unravel the processes by which these individuals cultivate and sustain their distinct online personas, while drawing insights from fellow influencers’ experiences. Its primary goal is to comprehend the experiences of Gen Z micro-influencers as they navigate establishing and nurturing their personal brand in the digital sphere, all while examining the impact of this role on their self-confidence.
Keywords: Micro-influencer; Social media; Public relations